Analyzing Framing Effecty by an Experiment among Students in Turkey - Hatime Kamilçelebi; Emre Ünal (Journal of Economic and Social Thought, 2014)
This study investigates the framing effect of experiments that conducted among students. The main aim of this work is to show the results of an experiment conducted in Turkey how could affect behavior of subjects who were students in banking and insurance business studies department. By expressing a particular topic in negative and positive way we could observe the behaviors. In conclusion, these subjects mainly focused on positive expression to avoid risks.
Keywords: D70; D80; 330; Behavioral economics; Framing effect; Risks; Choices